Tree density influences ecohydrological drivers of plant–water relations in a larch boreal forest in Siberia. Issue 7 (11th July 2019) - Kropp, Heather; Loranty, Michael M.; Natali, Susan M.; Kholodov, Alexander L.; Alexander, Heather D.; Zimov, Nikita S.; Mack, Michelle C.; Spawn, Seth A.
Abstract: Transpiration and stomatal conductance in deciduous needleleaf boreal forests of northern Siberia can be highly sensitive to water stress, permafrost thaw, and atmospheric dryness. Additionally, north‐eastern Siberian boreal forests are fire‐driven, and larch ( Larix spp.) are the sole tree species. We examined differences in tree water use, stand characteristics, and stomatal responses to environmental drivers between high and low tree density stands that burned 76 years ago in north‐eastern Siberia. Our results provide process‐level insight to climate feedbacks related to boreal forest productivity, water cycles, and permafrost across Arctic regions. The high density stand had shallower permafrost thaw depths and deeper moss layers than the low density stand. Rooting depths and shallow root biomass were similar between stands. Daily transpiration was higher on average in the high‐density stand 0.12 L m −2  day −1 (SE: 0.004) compared with the low density stand 0.10 L m −2  day −1 (SE: 0.001) throughout the abnormally wet summer of 2016. Transpiration rates tended to be similar at both stands during the dry period in 2017 in both stands of 0.10 L m −2  day −1 (SE: 0.002). The timing of precipitation impacted stomatal responses to environmental drivers, and the high density stand was more dependent on antecedent precipitation that occurred over longer periods in the past compared with the low density stand. Post‐fire tree density differences in plant–water relations may lead to different trajectories in plant mortality, water stress, and ecosystem water cycles across Siberian landscapes.